PERILAKU KONSUMEN PADA KEPUTUSAN PEMBELIAN AUDIO MOBIL: Studi Kasus Di Toko Cherly Audio - Cherly Dwi Qarlina (Universitas Methodist Indonesia, 2019)
This study aims to find out and get consumer behavior in-car audio purchasing decisions. The design of this study is descriptive and qualitative. The sampling technique in this study used snowball sampling techniques with criteria totaling three people, which will be the key informants namely Muslih, Gilang Amran, and Abinaya Pamungkas. The data analysis technique used is descriptive qualitative analysis with interactive analysis. The results of the study, according to the informants, found that consumer behavior in purchasing decisions based on the economic situation is if the higher income earned then the purchasing power level will be higher in the adjustment of expenditure needs and the selection of one's product to car audio purchase decisions in the Cherly Audio Shop, and vice versa. Based on lifestyle is someone's activity that is gathering with friends, the someone's interest that is because of price likes to change car audio and follow someone's trend and the opinion that is because of work, hobby, price, service, and personal experience. And based on perceptions is price, wide parking, ease of use and variety of products available. Perceptions are also stimulated by the existence of internal factors, namely the comfort of sound results, trust, and service. And also the external factors, namely product sophistication, friend invitation and unique audio features. The decision to purchase car audio is influenced by internal stimuli, namely looking for comfort and alternatives to avoid feeling bored and sleepy then the sources of information that is obtained from friends and brochures, likewise the purchasing decisions are influenced by prices. So that consumers respond to satisfaction and will act to recommend to their friends and will make repeat purchases after making a purchase decision. Car audio that is favored by consumers in the Cherly Audio Store is the subwoofer and speaker.